Pengaruh Model Pembelajaran Project Based Learning (PjBL) Terhadap Self Efficacy Dan Kemampuan Berpikir Kreatif Peserta Didik Kelas XI Pada Materi Larutan Penyangga Di SMAN 1 Mauponnggo - Baiyo, Anita Dhija; Muti’ah, Muti’ah; Ariani, Sunniarti (Chemistry Education Practice, 2025)
Problem-solving in chemistry requires support from various aspects, including psychological aspects such as self-efficacy and cognitive aspects such as creative thinking skills. This study aims to determine the effect of the Project-based Learning (PjBL) model on the self-efficacy and creative thinking skills of Grade XI students on the topic of buffer solutions at SMAN 1 Mauponggo. The research design used was a nonequivalent control group design, with purposive sampling as the sampling method, where participants were selected based on specific goals or criteria relevant to the research topic. The independent variable in this study was the Project-Based Learning (PjBL) model. Self-efficacy data were collected using a self-efficacy questionnaire. In contrast, creative thinking skills data were obtained through a test developed based on indicators of creative thinking skills (fluency, flexibility, originality, elaboration). Hypothesis testing was conducted using MANOVA. The results showed that both students' self-efficacy and creative thinking skills had an F-value of 15.198, which exceeded the F-table value of 4.05 at a significance level of 0.05. Based on these results, it can be concluded that the PjBL model has a significant effect on students’ self-efficacy and creative thinking skills.